Essentially unemployed: Potential implications of the COVID-19 crisis on wage inequality - Ansel Schiavone (The University of Utah, Department of Economics, 2020)
The aim of this paper is to determine how wage inequality is likely to be affected by the current COVID-19 pandemic. I first estimate the impact that social distancing will have on US state-level employment using pre-crisis industry data. I then consider the joint impact of states' unemployment benefit programs and the federal CARES Act on national inequality using representative sampling and Markov-Chain-Monte-Carlo estimations. I find that while wage inequality is likely to improve in the short-run with the added federal subsidy, allowing this support to expire prematurely will result in a worsening of pre-crisis wage inequality.
Keywords: E24; E27; C15; 330; Wage inequality; unemployment; COVID-19; Markov-Chain-Monte-Carlo; Gibbs sampling; structuralist method